Perimenopausal Pneumococcal Tubo-Ovarian Abscess – a Case Report and Review. Issue 1 (2004) - Seshadri, Srividya; Kirwan, John; Neal, Tim
Abstract : Background: Genital tract infections in females secondary to Streptococcus pneumoniae (pneumococcus) are unusual. Tubo-ovarian abscess resulting from such an infection is a rare occurrence and diagnosis is not always easy. This report demonstrates the problems of recognizing this condition and summarizes the pathomechanism, investigations leading to a diagnosis and the subsequent management. Case: A rare case of a tubo-ovarian abscess caused by pneumococcus, occurring in a previously healthy 48- year-old woman, is presented. The tubo-ovarian abscess may have developed insidiously and probably had an acute exacerbation prior to presentation. Conclusion: This case is unusual in that there were no identifiable initiating events for the source of the pneumococcal infection. Early recognition of a tubo-ovarian abscess is important in order to prevent the associated morbidity and mortality. This condition has the propensity to mimic a neoplasm.